AGROCLIMATIC EVALUATION OF THE CONDITIONS FOR FORMING THE YIELD OF CORN IN THE STEPPE ZONE OF UKRAINE FOR THE PERIOD UP TO 2050 - Belolybtsev А.И.; Dronova Е.А.; Аsаulyak И.Ф. (Hydrometeorology and ecology, 2023)
The estimation of agroclimatic conditions for the formation of maize productivity for the period up to 2050 is given. Recommendations for adaptation of technologies for growing corn and improving the conditions for crop formation under conditions of climate change.